962. Trends in Cervical Pre-cancers by Race and Ethnicity During the Human Papillomavirus Vaccine Era, HPV Vaccine Impact Monitoring Project (HPV-IMPACT), United States, 2008–2016 - Gargano, Julia (Open Forum Infect Dis, 2019)
BACKGROUND: Since human papillomavirus (HPV) vaccine introduction in the United States in 2006, cervical pre-cancer incidence has declined in young women, but pre-cancer trends have not been reported by race/ethnicity. We evaluated trends in cervical pre-cancers from 2008 to 2016 in non-Hispanic (NH) white, NH black, NH Asian, and Hispanic women identified through active population-based surveillance in the 5-site Human Papillomavirus Vaccine Impact Monitoring Project (HPV-IMPACT). METHODS: We analyzed data on cervical intraepithelial neoplasia (CIN) grades 2–3 and adenocarcinoma in situ (CIN2+) cases aged 20–39 years. Annual CIN2+ rates per 100,000 women were calculated stratified by race/ethnicity in 5-year age groups, using multiple imputation to account for 10% missing race/ethnicity data. Rates were also calculated using estimated numbers screened for cervical cancer to control for known declines in screening. Trends, evaluated using JoinPoint software, are presented as average annual percentage changes (AAPC) with 95% confidence intervals (CI). RESULTS: A total of 18,222 CIN2+ cases (62% NH white, 16% NH black, 16% Hispanic, 6% Asian) were reported from 2008 to 2016. CIN2+ rates among 20–24 year-olds declined significantly in all groups: NH white, AAPC: −14.2 (95% CI: −16.3, −12.1); NH black, AAPC: −15.5 (−19.5, −11.4); Asian, AAPC: −14.8 (−20.5, −8.8); Hispanic, AAPC: −14.3 (−17.9, −10.5). In 25–29 year olds, a significant decline was observed for NH whites only (AAPC: −2.4, [−4.0, −0.8]). No declines were seen in 30–34 or 35–39 year olds. Among screened 20–24 year-olds, significant but smaller declines were observed (AAPC: −9.8 to −8.4); no declines were observed in screened 25–29 year olds or older groups. CONCLUSION: In this evaluation of CIN2+ trends by race/ethnicity during the HPV vaccine era, the significant declines in 20–24 year olds across all groups, including among screened women, is consistent with equitable vaccine impact on CIN2+. DISCLOSURES: All Authors: No reported Disclosures.